PERSUASION, INTERACTION AND THE CONSTRUCTION OF KNOWLEDGE: REPRESENTING SELF AND OTHERS IN RESEARCH WRITING - Hyland, Ken (International Journal of English Studies, 2008)
It is now increasingly accepted that academic knowledge is closely related to the social practices of academic communities, and particularly to their discourses. Texts are persuasive only when they employ rhetorical conventions that colleagues find convincing, and in recent years corpus analyses have helped to underpin this social constructivist position and to reveal some of the ways this is achieved. In this paper I discuss the role of interaction in this process. Based on an analysis of 240 published research papers from eight disciplines and insider informant interviews, I explore the nature of interactive persuasion in this genre. I show here the importance of interaction in academic argument, suggest some of the ways this is achieved, and indicate how these choices reflect and construct disciplinary communities.